Effectiveness of prescribing physical activity in parks to improve health and wellbeing - the park prescription randomized controlled trial - MUELLER-RIEMENSCHNEIDER FALK (Springer Science and Business Media LLC, 2020)
10.1186/s12966-020-00941-8